2018
DOI: 10.1051/epjconf/201817702001
|View full text |Cite
|
Sign up to set email alerts
|

Delithiated states of layered cathode materials: doping and dispersion interaction effects on the structure

Abstract: Ni 10 CoAlO 24 model). The paper is aimed at independent elucidation of doping and dispersion interaction effects on the structural stability of cathode materials studied. For this purpose, the LNO and N 10 C 1 A 1 configurational spaces consisting of 87 and 4512 crystallographically independent configurations (obtained starting from 2×2×1 supercell of R3m structure of LNO) are optimized within a number of DFT models. Based on a comparison of the calculated dependencies for the lattice parameters with the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently, we have developed , an approach for sampling and structural description of the full CCSs of the doped Li­(Ni,Co,Al)­O 2 cathode material and combined it with machine learning (ML) techniques. We showed that the prediction of crystal structure formation energies resulted in a high accuracy (mean absolute error <2 meV/ion).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have developed , an approach for sampling and structural description of the full CCSs of the doped Li­(Ni,Co,Al)­O 2 cathode material and combined it with machine learning (ML) techniques. We showed that the prediction of crystal structure formation energies resulted in a high accuracy (mean absolute error <2 meV/ion).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the introduced criterion of successful energy estimation is not satisfied at the higher delithiation levels. Based on the results of DFT calculations [9,10], the apparent reason for such observation is dispersion interaction which can contribute significantly to the structure energies at high delithiation. The latter causes significant structural changes of the layered cathode materials altering the DFT-vdW energies with respect to that calculated within the electrostatic approach for the non-optimized NCA CCS.…”
Section: Conclusion and Remarksmentioning
confidence: 99%